Community assembly and potential function analysis of the endophyte in Eucommia ulmoides - Yunzhe Tang; Chunlian Tian; Di Yao; Shuai Yang; Linfang Shi; Langbo Yi; Qingzhong Peng (BMC Microbiology, 2024)
Abstract Endophytes play a pivotal role in protecting host plants from both biotic and abiotic stresses, promoting the production of active components (AC) and plant growth. However, the succession of the endophyte community in Eucommia ulmoides (E. ulmoides), particularly the community assembly and function, has not been extensively investigated. In this study, we employed high-throughput sequencing and bioinformatics tools to analyze endophyte diversity across different tree ages, parts, and periods. We examined the population differences, correlations, community assembly mechanisms, and functional roles of these endophytes. Functional predictions via PICRUSt2 revealed that most endophytic fungal functions were linked to biosynthesis, with significant differences in biosynthetic functional abundance across parts and periods. In contrast, the metabolic activity of endophytic bacteria remained stable across different periods and parts. Correlation analysis further confirmed a strong positive relationship between ACs and certain endophytic fungi. Among them, the fungal phyla Ascomycota and Basidiomycota were identified as key contributors to the metabolism of chlorogenic acid (CA), while Aucubin was significantly positively correlated with several endophytic bacteria. These findings provide valuable insights into the functional roles and community assembly mechanism of E. ulmoides endophytes, as well as their symbiotic relationships.